Thermal behaviour of expanded polystyrene based lightweight concrete sandwich panel at various temperatures - Koju, Surya Man (Journal of Science and Engineering, 2017)
Expanded Polystyrene (EPS) based lightweight concrete sandwich panel is a light weight building material that exhibits good thermal properties and is suitable for making thermally insulated building walls. This study contains experimental determination of thermal conductivity, overall heat transfer coefficient and thermal resistance of EPS based lightweight concrete sandwich panels. Resistive heating is used for performing thermal tests. Internal heat transfer is considered during experiment and the results are achieved by steady state heat transfer method. Thermal quality of sandwich panel with varying thicknesses is observed. Experiments are repeated with four types of source temperatures. All the samples are oven dried before taken into experimentation. The thermal results indicated that EPS based lightweight concrete sandwich panel poses overall heat transfer coefficient of 1.75 W/m2K, 2.06 W/m2K, 6.09 W/m2K and 6.54 W/m2K for 90 mm thick sandwich panel at low temperature, ambient temperature, high temperature and extreme temperature respectively.